El Rol de la formación en la construcción de comunidades participativas y autogestionarias para el buen vivir, aplicado en el proyecto Habitacional Alpallacta de la Cooperativa de Vivienda Alianza Solidaria. - López Giler, Sandra María (2014)
For Cooperative Housing Solidarity Alliance , the main objective is focused on the construction of cooperative communities , a concept that integrates : habitat, community and housing. Thus, to complete the construction of Alpallacta Project Cooperative implemented a training process designed to ensure harmonious coexistence and communal relationship between neighbors, community and nature. This process involved planned and systematic actions involving exercises work , theoretical contributions , critical reflection and evaluation of their application. This work shows that society contains ; in the first chapter a look at what are the institutions , organizations, social actors , social movements and community, how formative , educational processes play a key role in creating new type communities .